Characterization and expression of subtilases involved in grapevine resistance to Plasmopara viticola - Silva, Clemente da (2018)
Tese de mestrado em Biologia Molecular e Genética, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2017